An inverse association of dietary choline with atherosclerotic cardiovascular disease among US adults: a cross-sectional NHANES analysis - Hui Lin; Zuoquan Zhong; Chuanjin Zhang; Xiaojun Jin; Xuchen Qi; Jiangfang Lian (BMC, 2024)
Abstract Background The role of diet choline in atherosclerotic cardiovascular disease (ASCVD) is uncertain. Findings from animal experiments are contradictory while there is a lack of clinical investigations. This study aimed to investigate the association between choline intake and ASCVD based on individuals from the National Health and Nutrition Examination Survey (NHANES) database. Methods This cross-sectional study was conducted in 5525 individuals from the NHANES between 2011 and 2018. Participants were categorized into the ASCVD (n = 5015) and non-ASCVD (n = 510) groups. Univariable and multivariable-adjusted regression analyses were employed to investigate the relationship between diet choline and pertinent covariates. Logistic regression analysis and restricted cubic spline analysis were used to evaluate the association between choline intake and ASCVD. Results ASCVD participants had higher choline intake compared to those without ASCVD. In the higher tertiles of choline intake, there was a greater proportion of males, married individuals, highly educated individuals, and those with increased physical activity, but a lower proportion of smokers and drinkers. In the higher tertiles of choline intake, a lower proportion of individuals had a history of congestive heart failure and stroke. After adjusting for age, gender, race, ethnicity, and physical activity, an inverse association between choline intake and heart disease, stroke, and ASCVD was found. A restricted cubic spline analysis showed a mirrored J-shaped relationship between choline and ASCVD, stroke and congestive heart failure in males. There was no association between dietary choline and metabolic syndrome. Conclusion An inverse association was observed between choline intake and ASVCD among U.S. adults. Further large longitudinal studies are needed to test the causal relationship of choline and ASVCD.